2013
DOI: 10.1186/1745-6215-14-264
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of a social network intervention for heroin users in opiate substitution treatment: study protocol for a randomized controlled trial

Abstract: BackgroundResearch indicates that 3% of people receiving opiate substitution treatment (OST) in the UK manage to achieve abstinence from all prescribed and illicit drugs within 3 years of commencing treatment, and there is concern that treatment services have become skilled at engaging people but not at helping them to enter a stage of recovery and drug abstinence. The National Treatment Agency for Substance Misuse recommends the involvement of families and wider social networks in supporting drug users’ psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The full trial protocol can be found elsewhere [42]. The two psychological interventions were a brief adapted version of 'Social Behaviour and Network Therapy (B-SBNT)', which actively aimed to involve social network members in the process of helping participants achieve their personal goals [43,44], and 'Personal Goal Setting', which set specific goals and monitored achievement on an individual basis [45].…”
Section: Data Sourcementioning
confidence: 99%
“…The full trial protocol can be found elsewhere [42]. The two psychological interventions were a brief adapted version of 'Social Behaviour and Network Therapy (B-SBNT)', which actively aimed to involve social network members in the process of helping participants achieve their personal goals [43,44], and 'Personal Goal Setting', which set specific goals and monitored achievement on an individual basis [45].…”
Section: Data Sourcementioning
confidence: 99%
“…Detailed information about the study design and participants can be found elsewhere [40]. In brief, this was a pilot study with a pragmatic, multicentre, randomised parallel group design comparing two active psychological interventions, offered as adjunct to usual care, with usual care.…”
Section: Trial Design and Participantsmentioning
confidence: 99%
“…One of the most effective psychotherapies for addiction is coping and social skills training CSST), which teaches social strategies for navigating social interactions, addressing interpersonal problems, and managing craving in response to social/drug-related contexts and cues (Monti and O'Leary, 1999). In addition, new behavioral interventions for addicted patients are centered around social networks (Day et al, 2013), which are an important modulator of drug use and relapse (Mundt, 2011) preference for the context test. Approach to the star-cue was calculated to measure sign-tracking for the cue test.…”
Section: Discussionmentioning
confidence: 99%